Lithuanian Congress of Psychology „Atlas of Psychology“ - Lazauskaitė-Zabielskė, Jurgita; Zamalijeva, Olga (Vilnius University Proceedings, 2025)
The Lithuanian Congress of Psychology is an annual event organised by the Lithuanian Psychological Association in cooperation with various Lithuanian higher education institutions. This year, the Institute of Psychology of the Faculty of Philosophy at Vilnius University was responsible for the implementation of the event entitled "Atlas of Psychology" (April 25-26, 2025), which was held for the third time at Vilnius University. It is the only event that brings together all psychologists in Lithuania, regardless of their specialisation, type of work or experience. Its main aim is to create a platform to share the latest research results, professional knowledge and experience, to improve their competences and to build collaborative relationships. This publication presents abstracts of papers presented at the Lithuanian Congress of Psychology, peer-reviewed by the Scientific Committee, and presented by researchers and practitioners from Lithuanian and foreign universities.